2017
DOI: 10.7717/peerj.4179
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum pesticide application alters natural enemy communities and may facilitate secondary pest outbreaks

Abstract: BackgroundPesticide application is the dominant control method for arthropod pests in broad-acre arable systems. In Australia, organophosphate pesticides are often applied either prophylactically, or reactively, including at higher concentrations, to control crop establishment pests such as false wireworms and earth mite species. Organophosphates are reported to be disruptive to beneficial species, such as natural enemies, but this has not been widely assessed in Australian systems. Neither has the risk that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…Farmers can manage slugs using baits, which can include active ingredients like metaldehyde (2,4,6,8‐tetramethyl‐1,3,5,7‐tetroxocane) or iron; however, baits can be expensive (Douglas and Tooker, 2012), and may not persist in typical wet spring conditions due to water solubility (Bailey, 2002). Slug damage can also be exacerbated by insecticides, including seed coatings or broadcast applications, both of which tend to reduce populations of predators that eat slugs (Douglas et al, 2014; Hill et al, 2017).…”
mentioning
confidence: 99%
“…Farmers can manage slugs using baits, which can include active ingredients like metaldehyde (2,4,6,8‐tetramethyl‐1,3,5,7‐tetroxocane) or iron; however, baits can be expensive (Douglas and Tooker, 2012), and may not persist in typical wet spring conditions due to water solubility (Bailey, 2002). Slug damage can also be exacerbated by insecticides, including seed coatings or broadcast applications, both of which tend to reduce populations of predators that eat slugs (Douglas et al, 2014; Hill et al, 2017).…”
mentioning
confidence: 99%
“…This indicates that the application of various synthetic pesticides in conventional coffee plantations has a negative impact on Arthropods which acts as a natural enemy in coffee plants. Quite a lot of broad spectrum pesticides such as organophosphate have disrupted the existence of various beneficial species, such as natural enemies and have also caused secondary pest outbreaks [12]. In our previous study Hamdi et al, (2015) we found a parasitoid species that was once released in a coffee plantation in Aceh Tengah Regency, namely Phoropo nasuta (Hymenoptera: Bethylidae).…”
Section: Observationmentioning
confidence: 91%
“…Integrated Pest Management (IPM) has been successfully applied as a strategy across several agricultural production systems in order to optimise invertebrate pest management, encourage the judicious use of pesticides (to mitigate problems associated with resistant pest populations and environmental contamination) and improve sustainability (Ellsworth & Martinez-Carrillo 2001). Yet there are many systems for which IPM adoption has been slow or piecemeal, and farmers are still heavily reliant on prophylactic application of broad-spectrum insecticides (Zalucki et al 2009;Zalucki et al 2015;Hill et al 2017). IPM has a strong theoretical foundation in the population ecology of herbivores, and especially how herbivore abundance is related to the interactions between bottom-up resources (e.g.…”
Section: Introductionmentioning
confidence: 99%